Алгоритм расчета параметров приемника излучения КЭСР онкологических процессов на основе анализа инфракрасного спектра крови = The algorithm for calculating the parameters of a radiation oncology correlation-extreme recognition system (CERS) processes base - Chuhraev, N. V.; Zukow, W. (Journal of Education, Health and Sport, 2015)
Chuhraev N. V., Zukow W. Алгоритм расчета параметров приемника излучения КЭСР онкологических процессов на основе анализа инфракрасного спектра крови = The algorithm for calculating the parameters of a radiation oncology correlation-extreme recognition system (CERS) processes based on the analysis of the infrared spectrum of blood. Journal of Education, Health and Sport. 2015;5(6):225-240. ISSN 2391-8306. DOI 10.5281/zenodo.18542 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%286%29%3A225-240 https://pbn.nauka.gov.pl/works/565578 http://dx.doi.org/10.5281/zenodo.18542 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 21.04.2015. Revised 28.05.2015. Accepted: 10.06.2015. Алгоритм расчета параметров приемника излучения КЭСР онкологических процессов на основе анализа инфракрасного спектра крови The algorithm for calculating the parameters of a radiation oncology correlation-extreme recognition system (CERS) processes based on the analysis of the infrared spectrum of blood Чухраев Н. В., Zukow W. Chuhraev N. V., Zukow W. НИИ МИТ, Киев, Ukraine Kazimierz Wielki University, Bydgoszcz, Poland MIT RESEARCH INSTITUTE, Kiev, Ukraine Kazimierz Wielki University, Bydgoszcz, Poland Аннотация В работе рассмотрен алгоритм выбора и расчета параметров приемника излучения корреляционно экстремальной системы распознавания онкологических процессов на основе анализа инфракрасного спектра крови. Abstract The algorithm of choice and calculation of parameters of receiver of radiation correlation of the extreme system of recognition of oncologic processes on the basis of analysis of infra-red spectrum of blood is considered in work. Резюме У роботі розглянутий алгоритм вибору і розрахунку параметрів приймача випромінювання кореляційно екстремальної системи розпізнавання онкологічних процесів на основі аналізу інфрачервоного спектру крові. Ключевые слова: алгоритм расчета, приемник излучения КЭСР, онкологическиe процессы, анализ инфракрасного спектра, кровь. Key word: the algorithm for calculating, parameters of a radiation, oncology correlation-extreme recognition system (CERS), oncologic processes, analysis of the infrared spectrum, blood.